Relationship between maternal hemoglobin and birthweight in Antioquia, Colombia (2021)
ABSTRACT: Objectives: to determine the relationship between maternal hemoglobin (HbM) per gestational trimester and birthweight (BW). Methods: this was an analytical, cross-sectional observational study that included the prenatal records of 494 pregnant women who delivered live newborns in the Department of Antioquia. The maternal health data collected included HbM and BW, and gynecological and obstetric, anthropometric, and maternal health-related data. The Mann–Whitney U test was applied, supplemented by effect size (ES) to compare the study groups. Results: HbM in the third trimester was significantly associated with BW (p=0.029).It showed a significant effect size on BW as follows: first trimester: ES=0.44 (CI95%=0.183–0.697); second trimester: ES=0.49 (CI95%= 0.187–0.79); and third trimester: ES=0.43 (CI95% = 0.202–0.658). Maternal anemia was 4.2%, 11.2%, and 21.4% in the first, second, and third trimester, respectively. Conclusions: as it is an inexpensive indicator and easy to determine, the timely monitoring and assessment of HbM is required owing to its importance in maternal and neonatal health, quality of life, and human capital development. Key words: Birth weight, Anemia, Maternal hemoglobin, Pregnancy, Prenatal